2017
DOI: 10.1259/bjrcr.20150358
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal pneumonia: the great mimicker

Abstract: Cryptococcal pneumonia is a fungal infection caused by Cryptococcus neoformans predominantly in immunosuppressed individuals and rarely in the immunocompetent population. In this study, we describe the varied radiological presentations in three patients, both immunosuppressed and immunocompetent individuals. The varied imaging presentations pose a great challenge for the radiologist and the clinician. The imaging findings mimic other diseases and it might make the diagnosis difficult purely on radiological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Comparatively to the other two types of infections, cryptococcal pneumonia is found in all adult age group patients. 29 A previous 20-year retrospective study from China reported a mean age of 49.3 (SD: 14.3) for cryptococcal pneumonia patients. 24 The occurrence of cryptococcal pneumonia in all age patients is solely related to the subject’s weakened immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively to the other two types of infections, cryptococcal pneumonia is found in all adult age group patients. 29 A previous 20-year retrospective study from China reported a mean age of 49.3 (SD: 14.3) for cryptococcal pneumonia patients. 24 The occurrence of cryptococcal pneumonia in all age patients is solely related to the subject’s weakened immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, there was a disseminated miliary/reticulonodular pattern which was diagnosed as cryptococcal pneumonia after axillary lymph node biopsy. It was concluded that in immunocompromised patients with multiple pulmonary nodules, cryptococcal pneumonia, Pneumocystis carinii pneumonia, and mycobacterial infections should be considered in the differential diagnosis of pulmonary infections [23].…”
Section: Discussionmentioning
confidence: 99%
“…The imaging features of cryptococcal infection tend to mimic other pathological conditions. A case report reviewing the presentation among two immunosuppressed patients and one immunocompetent patient revealed the difficulty in diagnosing cryptococcal pneumonia based on radiological findings alone [ 6 ]. One immunocompromised patient presented with nodular opacities in bilateral lung fields on chest X-ray and enlarged lymph nodes in the mediastinum and axillary regions on CT scan [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A case report reviewing the presentation among two immunosuppressed patients and one immunocompetent patient revealed the difficulty in diagnosing cryptococcal pneumonia based on radiological findings alone [ 6 ]. One immunocompromised patient presented with nodular opacities in bilateral lung fields on chest X-ray and enlarged lymph nodes in the mediastinum and axillary regions on CT scan [ 6 ]. A CT scan of the thorax in the second immunocompromised patient demonstrated a mass in the right lower lobe of the lungs mimicking a malignant lesion [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation